2019
DOI: 10.1158/0008-5472.can-18-3933
|View full text |Cite
|
Sign up to set email alerts
|

The HPV16 Genome Is Stable in Women Who Progress to In Situ or Invasive Cervical Cancer: A Prospective Population-Based Study

Abstract: The human papillomavirus (HPV) rate of evolution is essential for cancer-preventive strategies targeting HPV. We analyzed variability over time in a prospective, populationbased nested case-control study of in situ (CIS) and invasive squamous cervical cancer (SCC). Among 757,690 women who participated in cervical screening in Sweden during 1969 to 2002, we identified 94 women who had HPV16 persistence in two serial cervical screening samples (median 24 months apart, range 0.5-178 months) and later were diagnos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
4
5
0
Order By: Relevance
“…We found a total of 3747 MNVs in the 131 samples, being in line with studies reporting a high number of HPV variation at the population level [20,42,43], within infected hosts [10,11,30]. A recent study on HPV16 genome stability analysed possible HPV16 sublineage co-infections and observed 20-38 variants in each sample [44], corresponding to the mean numbers of MNVs in this study. The variation was reported not to be due to co-infections but interpretation of the nucleotide variation source was not further elaborated [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found a total of 3747 MNVs in the 131 samples, being in line with studies reporting a high number of HPV variation at the population level [20,42,43], within infected hosts [10,11,30]. A recent study on HPV16 genome stability analysed possible HPV16 sublineage co-infections and observed 20-38 variants in each sample [44], corresponding to the mean numbers of MNVs in this study. The variation was reported not to be due to co-infections but interpretation of the nucleotide variation source was not further elaborated [44].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study on HPV16 genome stability analysed possible HPV16 sublineage co-infections and observed 20–38 variants in each sample [44], corresponding to the mean numbers of MNVs in this study. The variation was reported not to be due to co-infections but interpretation of the nucleotide variation source was not further elaborated [44].…”
Section: Discussionmentioning
confidence: 99%
“…We found a total of 3669 MNVs in the 131 samples, being in line with studies reporting a high number of HPV variation at the population level [ 24 , 46 , 47 ], within infected hosts [ 11 , 12 , 34 ]. A recent study on HPV16 genome stability analysed possible HPV16 sublineage co-infections and observed 20–38 variants in each sample [ 48 ], corresponding to the mean numbers of MNVs in this study. The variation was reported not to be due to co-infections, but interpretation of the nucleotide variation source was not further elaborated [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on HPV16 genome stability analysed possible HPV16 sublineage co-infections and observed 20–38 variants in each sample [ 48 ], corresponding to the mean numbers of MNVs in this study. The variation was reported not to be due to co-infections, but interpretation of the nucleotide variation source was not further elaborated [ 48 ]. The prevalence of sub-lineage co-infections is expected to be low [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study including genomic analysis of HPV16 on serial cervical samples from precancer/cancer cases revealed that 56% of the women tested had an identical viral genomic sequence in two consecutive samples (the median time between sampling was 24 months) (Arroyo-Muhr et al, 2019). Moreover, the estimated substitution rate was almost zero substitutions/site/year, suggesting that HPV16 genomic sequences are extremely stable in most cases of persistent infections.…”
Section: Discussionmentioning
confidence: 99%